(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: The expanding spectrum of therapeutic options for patients with Obstructive /surgical jaundice makes it necessary for the surgeon to precisely assess the etiology, location, level and extent of disease before operation. Aims were to compare the diagnostic accuracy, sensitivity and specificity of different imaging techniques like ultrasonography (USG), Computed tomography (CT) and Magnetic Resonance Cholangiopancreatography (MRCP) and Endoscopic Retrograde Cholangiopancreatography (ERCP) in evaluation of patients with malignant obstructive jaundice and correlation of histopathological findings after surgical/ therapeutic intervention. Methods: It was a prospective observational study conducted in the Department of General Surgery and Hepatobilliary unit, Dhaka Medical College Hospital and Bangabandhu Sheikh Mujib Medical University, Dhaka during January 2015 to December 2015 for duration of one year to find out the role of different imaging techniques in diagnosis of malignant lesions causing obstructive jaundice in 50 cases who fulfilled the inclusion criteria. Initial USG evaluation was followed by CT scan, MRCP and ERCP. The results were read by radiologists blinded to other imaging findings. Surgically fit patients with a stage of resectability should be offered the option of surgical resection for cure. For unresectable malignancies, the choice is between surgical palliation/bypass and ERCP with drainage. The characteristic surgical findings or ERCP features and histopathological diagnosis were recorded methodically as final. Results: Malignant obstructive jaundice is the commonest amongst the males and mean age was 47.56 ± 13.191 and the commonest etiology was Ca head of pancreas (30%). Diagnostic accuracy of MRCP (98%) in the diagnosis of malignant obstructive jaundice was relatively high (98%) as compared to ERCP (89.5%), CT (91.43%), USG (89.97%) in malignant obstructive jaundice respectively. In the diagnosis of malignant diseases, MRCP was more sensitive (95.83%) as compared to ERCP (89%), CT scan (91.67%) and ultrasonography (78.17%). Regarding specificity MRCP (100%) was the high in comparison among ERCP (94%), CT (90.91%) and USG (96.15%).Conclusion: It is concluded that malignant obstructive jaundice is the commonest amongst the males. Ca head of pancreas was the commonest malignant etiology in malignant obstructive jaundice. MRCP was superior to among USG, CT scan or ERCP in studying the malignant lesions. J Bangladesh Coll Phys Surg 2021; 39: 233-240